Sikap, Jarak Pelayanan Kesehatan dan Dukungan Orang Tua untuk Kesediaan Vaksinasi HPV pada Remaja - Dinda Salmahella; Lutfi Agus Salim; Muhammad Atoillah Isfandiari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to see the relationship between attitude, distance to health services, and parental support with the willingness to the HPV vaccine in adolescents. This research method is cross-sectional. The results of this study show that attitude (p=0.000) [PR= 2.234, 95% CI 1.512-3.300] and parental support (p=0.028) [PR=1.549, 95% CI 1.041-2.306] have a significant relationship with willingness to vaccinate HPV. Meanwhile, the distance from home to health services (p=0.151) [PR=0.729, 95% CI 0.464-1.145] had no relationship with willingness to vaccinate against HPV. In conclusion, adolescents with good parental attitudes and support are more likely to be willing to vaccinate against HPV. Keywords: Human Papilloma Virus (HPV), Cervical Cancer, Adolescents, Attitudes, Vaccines